Risk factors associated with deep vein thrombosis in COVID‐19 patients. Issue 2 (18th March 2021) - Wang, Bin; Zhang, Li; Yin, Shanye; Deng, Wenjun; Xie, Mingxing
Abstract: Abstract : Here we identified age, D‐Dimer and CK‐MB as independent risk factors of DVT in COVID‐19 patients. The combination of age, D‐Dimer and CK‐MB yielded a sensitivity of 79.81% and a specificity of 73.20% to predict DVT events.